Adiwiyata Program Implementation Realizes Environmentally Conscious School Governance: Implementasi Program Adiwiyata Mewujudkan Tata Kelola Sekolah Berwawasan Lingkungan - Dona Amalia Wardana; Lailul Mursyidah; Muhammad Evan Firzatulloh Y; Mu’afah Nur Romadhoni; Aprillia Hartiningtyas (Proceedings of The ICECRS, 2025)
General Background A healthy and sustainable environment serves as the fundamental foundation for human civilization and ecological continuity. Specific Background In Indonesia, environmental education is mainstreamed through the Adiwiyata program to foster ecological care and sustainable practices within educational institutions. Knowledge Gap Although the program aims to cultivate ecological awareness, practical implementation frequently encounters severe constraints regarding limited financial resources, insufficient infrastructure, and inadequate socialization or technical training for new organizational teams. Aims This qualitative case study analyzes the implementation of the Adiwiyata program at SMAN 1 Wonoayu to evaluate governance, accountability, and operational challenges. Results Findings reveal that while the program operates effectively through structured organizational units and diverse environmental activities, financial limitations restrict facility provisioning and plant breeding socialization remains insufficient. Novelty This research specifically identifies the operational friction caused by self-funded plant sales and decentralized seedling practices within resource-constrained secondary school environments. Implications Educational authorities must increase budget allocations and strengthen technical training workshops to optimize environmental conservation participation among all school residents. Highlights: limited financial resources and restricted funding sources constrain the provisioning of adequate environmental facilities and infrastructure inadequate socialization and technical direction regarding plant breeding hinder optimal program execution by newly assigned teams structured organizational units successfully coordinate daily ecological activities despite prevailing budgetary and resource limitations Keywords: Adiwiyata Program, Policy Implementation, Environmental Education, Sustainable Schools, Ecological Governance